(untitled) (Revista Inclusiones, 2018)
This study conducts the cost-benefit analysis of a new product developed from by-product of organic rice. The raw material is organic broken-milk rice and the new developing product is organic rice pudding. The primary data for cost benefit analysis were obtained from multi sector of rice supply chain, for instant, farmers, retailers and processed entrepreneurs. In addition, secondary data from literature review were included. The cost benefit analysis carried out under several assumptions on the life span of the project, for example, growth hypothesis, capital structure, cash collection and payment period. The result of the study revealed that payback period (PB) is 2 years and 7 months (940 days), net present value (NPV),based on 8% of discount rate, is 3,008,099 Thai Baht (95,500 dollar) and internal rate of return on investment (IRR) is 22.73% that the organic rice pudding has possibility and potential for new product investment. This research is helpful on a practical of significant economic for new product development (NPD).